Norwegian Secondary School Teachers’ Reflections on Models for Physical Activity During Schooltime: A Longitudinal Intervention Study - Lomsdal, Sondre Arntzen; Lyngstad, Idar Kristian; Lagestad, Pål Arild (Frontiers in Education, 2022)
To prevent the negative trend when it comes to physical activity (PA) among youth, schools have been promoted as an appropriate arena for facilitating it. This study focuses on Norwegian secondary school teachers’ perceptions in interviews before, during and after a PA intervention where various PA models are implemented in secondary school. An important finding appears to be that an implementation of PA must consider the complexity of the teacher’s practice, the diversity of students and the need for flexibility among teachers in their daily practice. Our study finds that facilitating PA in secondary school by using several methods is seen by the teachers as the preferable approach, and this supports the idea of a whole-school approach. Future research should focus on interventions where teachers gain experience of all the models aimed at implementing PA in school.